Decision-making model for outsourcing software development providers selection - Urekwere, Orlu Glory (2020)
The implementation of outsourcing software provider selection models in public sector has been rapidly increasing in the last few years. This is because of the necessity for organizations to establish IT alignment in their projects to deliver services and enhance sustainability. However, the outsourcing software provider selection processes face several challenges related to human perceptions such as the decision makers’ intuition, knowledge and experience, impreciseness, and vagueness in public sector. Also, outsourcing selection process, still have gaps in research despite the various researches being executed due to lack of empirical evidence regarding inappropriate selection of IT provider. Therefore, there is need to conduct more studies on how significant factors influence outsourcing selection process in public sector. Considering the significance of a clear standard for decision making in the selection of outsourced software providers in IT services, this research proposed a model by which this problem can be improved through the efficacy of the selection processes. Specifically, this research objectives are: to identify and prioritize influential factors for the decision making in outsourcing provider selection process, to propose a model for decision making in outsourcing provider selection in public sector, to validate the model against human perceptions and uncertainty through a prototype. The research scope is based on Malaysian outsourcing organizations that deal with outsourcing software selection processes. Quantitative research was adopted in this research thus, a pilot study was carried out from 33 respondents in Malaysian outsourcing organizations and another 133 respondents from a conducted empirical study. The developed decision outsourcing software selection model for public sector considers six criteria which are: development capability, product quality, delivery time, cost, client’s satisfaction, and service quality. The fuzzy logic technique supports the decision making procedure by assigning weightage, then evaluating and ranking the software providers. Afterward, three experts validated the model by verifying it in their outsourcing software provider selection processes; the model was shown to improve the chances of IT practitioners for selecting the most suitable software providers in Malaysian organizations.